The "konj-e qana'at" is other than the "ganj-e qana'at" - Mohammad Pourhamdollah (مطالعات زبانی و بلاغی, 2021)
Ahmad Mahdavi Damghani believes that in the Persian language, there is no combination called the konj-e qana'at and that what is printed in the literary texts, called konj-e qana'at, is originally the ganj-e qana'at; in his opinion, there is no relation between the words konj and qana'at; and the konj-e gana'at is a well-known misconception that was created owing to the inadvertent scribes and errors of the editors. In this research, we have tried to study the relationship between the words konj and qana'at in the context of mystical poetry and have tried to show that konj-e qana'at is not a well-known misconception, and it is other than the ganj-e qana'at. The "konj-e qana'at" and "ganj-e qana'at" are two separate combinations that have been used many times in Persian poetry. Konj-e qana'at is a metaphorical combination that is rooted in the mystical worldview and ganj-e qana'at is an analogic combination taken from the Prophet's hadis.